Economic burden of expected epidemiological changes in diseases related to tobacco, Mexico Impacto econômico das mudanças epidemiológicas esperadas nas doenças associadas ao tabaco, México - Armando Arredondo; Carlos Carrillo; Alexis Zuñiga (Universidade de São Paulo, 2007)
OBJECTIVE: To determine health care costs and economic burden of epidemiological changes in diseases related to tobacco consumption. METHODS: A time-series analysis in Mexico (1994-2005) was carried out on seven health interventions: chronic obstructive pulmonary diseases, lung cancer with and without surgical intervention, asthma in smokers and non-smokers, full treatment course with nicotine gum, and full treatment course with nicotine patch. According with Box-Jenkins methodology, probabilistic models were developed to forecast the expected changes in the epidemiologic profile and the expected changes in health care services required for selected interventions. Health care costs were estimated following the instrumentation methods and validated with consensus technique. RESULTS: A comparison of the economic impact in 2006 vs. 2008 showed 20-90% increase in expected cases depending on the disease (p<0.05), and 25-93% increase in financial requirements (p<0.01). The study data suggest that changes in the demand for health services for patients with respiratory diseases related to tobacco consumption will continue showing an increasing trend. CONCLUSIONS: In economic terms, the growing number of cases expected during the study period indicates a process of internal competition and adds an element of intrinsic competition in the management of preventive and curative interventions. The study results support the assumption that if preventive programs remain unchanged, the increasing demands for curative health care may cause great financial and management challenges to the health care system of middle-income countries like Mexico. OBJETIVO: Avaliar os custos da atenção médica a doenças associadas ao tabagismo e o impacto econômico das mudanças epidemiológicas. MÉTODOS: Análise de série temporal no México (1994-2005) de sete intervenções médicas em relação a: doença pulmonar obstrutiva crônica, câncer de pulmão com e sem intervenção cirúrgica, asma bronquial em fumantes e não-fumantes, tratamento com adesivos para deixar de fumar, tratamento com goma de mascar. As mudanças epidemiológicas esperadas e as necessidades financeiras para atender a demanda de serviços foram avaliadas pelos modelos probabilísticos de Box-Jenkins. Os custos foram determinados de acordo com método de instrumentação e a técnica de consenso. RESULTADOS: A comparação do impacto das mudanças epidemiológicas previstas para 2006 e 2008 mostrou incremento de 20% a 90%, dependendo do tipo de intervenção. O incremento nos custos da atenção médica foi de 25% a 93%. Há indícios que a demanda de serviços de saúde para as intervenções investigadas continuarão aumentando. CONCLUSÕES: Em termos econômicos, o aumento na quantidade de casos esperados refletem um fenômeno de competição interna em relação ao uso dos recursos adicionais entre atividades de promoção e prevenção da saúde relacionada ao tabagismo. Se não houver mudanças nos programas de prevenção, haverão desafios econômicos de alto impacto no financiamento dos sistemas de saúde.